Putting student partnership and collaboration centre-stage in a research-led context: A case study of the Summer Undergraduate Research Fellowship programme at Xi’an Jiaotong-Liverpool University - Huijser, Henk; Wilson, James; Wu, Yao; Qiu, Shuang; Wang, Kangxin; Li, Shun; Chen, Wenye; Kouwenhoven, M.B.N. (International Journal for Students as Partners, 2019)
In this case study, we evaluated the Summer Undergraduate Research Fellowship (SURF) initiative at Xi’an Jiaotong-Liverpool University (XJTLU), an extracurricular programme that focuses on academic staff-student partnerships and collaborations. While not directly integrated into university degree programmes, SURF provides students with the opportunity to develop practical research skills related to knowledge they have acquired in class. Participating students receive an authentic research experience, which involves collaboration on research projects with academic staff. All students are required to present results of their projects at a public poster presentation event organised by the university. This case study is a partnership between Academic Enhancement Centre (AEC) staff, who organize and run SURF, SURF students, and a lecturer (M.B.N. Kouwenhoven), and it presents a reflection on their experiences of the SURF programme, and in particular on the notions of partnership and collaboration and the potential tension between those two concepts.